Preparation technology of fluorescent and magnetic bifunctional three-color flag-like micron fiber
Through electrospinning technology combined with two parallel electrospinning technology and uniaxial electrospinning technology, a tricolor flag-like micron fiber was constructed, which solved the problem that perovskite quantum dots and magnetic substances in the prior art was difficult to achieve excellent performance at the same time, and achieved the fluorescent magnetic dual-functional characteristics of the material.
Patent Information
- Application Number
- CN202510046178.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-15
AI Technical Summary
The prior art is difficult to achieve the fluorescence performance of perovskite quantum dots and the magnetic properties of magnetic substances at the same time, and the two affect each other, resulting in poor material performance.
Using electrospinning technology, a new conjugated electrospinning technology combined with two parallel electrospinning technology and uniaxial electrospinning technology is constructed to achieve effective separation and integration of perovskite quantum dots and magnetic substances.
The excellent fluorescence characteristics and good magnetic properties of the material are achieved, and the adverse mutual influence between fluorescence and magnetism is avoided, and a fluorescent magnetic bifunctional material with good performance is obtained.
Smart Images

Figure CN119824563A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fiber material preparation, in particular to a preparation technology of fluorescent magnetic dual-functional tricolor flag type micron fiber. Background Art
[0002] The preparation and performance research of micro-nano fibers with special structures is currently one of the frontier hotspots in the research of chemistry, materials science and condensed matter physics, etc. People attach great importance to them because of their novel structure and unique optical, electrical and magnetic properties.
[0003] The three stripes in the tricolor flag represent different meanings. Similarly, three different chemical compositions have three distinct partition structures in the same micron fiber, each with three properties. For example, one side of the fiber has green luminescence, the middle fiber has magnetism, and the other side of the fiber has red luminescence, that is, a micron fiber with a fiber / / fiber / / fiber structure is formed. The morphology of such micron fibers is similar to the tricolor flag. We call it a tricolor flag-like micron fiber. This special structure of micron fibers has dual functional properties of fluorescence and magnetism.
[0004] Multifunctional micro-nanomaterials have broader application prospects than single-functional micro-nanomaterials. Micro-nanomaterials with dual functions of fluorescence and magnetism are typical important multifunctional materials and have attracted great attention from researchers. Existing studies have shown that if the dark-colored cobalt ferrite CoFe 2 O 4 When nanocrystals are directly blended with luminescent perovskite quantum dots, the luminescence intensity of the perovskite quantum dots will be significantly reduced. At the same time, if the two perovskite quantum dots are directly blended, new perovskite quantum dots will be generated due to the exchange of halogen anions, thereby affecting the fluorescence properties of the material. Therefore, if a dual-functional material with good fluorescence and magnetic properties is to be obtained, it is necessary to: (1) effectively separate the dark-colored magnetic material from the perovskite quantum dots; (2) the two perovskite quantum dots cannot be directly blended and must be effectively separated. Therefore, for multifunctional materials, it is crucial to design and construct suitable building blocks. The one-dimensional tricolor flag-like micron fiber has three independent partitions, which can assemble the two perovskite quantum dots and magnetic materials into three regions respectively, realizing a high degree of integration of the three functions at the microscopic level, and being independent of each other, reducing the adverse mutual influence between fluorescence and magnetism, thereby obtaining a macroscopic fluorescent magnetic dual-functional material with good performance.
[0005] Cobalt ferrite CoFe 2 O 4 It is an important and widely used magnetic material. People have successfully prepared CoFe by various methods, such as precipitation method, sol-gel method, hydrothermal and solvothermal method, electrospinning method, etc. 2 O 4Nanomaterials such as nanocrystals and nanowires have relatively mature technologies. Under ultraviolet light excitation, CsPbBr 3 and CsPb(Br 0.06 / I 0.94 ) 3 Perovskite quantum dots emit strong green and red fluorescence respectively, and the technology of preparing these quantum dots by hot injection is also relatively mature. Polystyrene PS is a commonly used polymer material with excellent performance. 2 O 4 Nanocrystals, perovskite quantum dots and PS are ideal choices for constructing fluorescent and magnetic dual-functional materials.
[0006] U.S. Patent No. 1975504 discloses a technical solution for electrospinning, which is an effective method for preparing continuous micro-nano fibers with macroscopic length. It was first proposed by Formhals in 1934. This method is mainly used to prepare polymer micro-nano fibers. Its characteristic is that the charged polymer solution or melt is pulled by the electrostatic force in the electrostatic field and ejected from the nozzle to the opposite receiving screen, thereby achieving wire drawing. Then, the solvent evaporates at room temperature, or the melt is cooled to room temperature and solidified to obtain micro-nano fibers. QZYu, et al. prepared polyaniline PANI nanofibers using electrospinning technology [Mater. Sci. Eng. B, 2008, 150, 70-76]; Dong Xiangting et al. used a uniaxial spinneret and electrospinning technology to prepare PAN / Eu(BA) 3 phen composite luminescent nanofibers [New Chemical Materials, 2008, 36(9), 49-52]; Wang Ce et al. prepared polyvinyl pyrrolidone / ferroferric oxide magnetic composite nanofibers using a single spinneret and electrospinning [Journal of Chemistry in Universities, 2006, 27(10), 2002-2004]; Qingbiao Yang, et al. prepared Fe 2 O 3 nanoparticles / Eu(DBM) 3 (Bath) / PAN composite dual-functional magneto-optical nanofibers [Journal of Colloid and Interface Science, 2010, 350, 396-401]; Dong Xiangting et al. prepared Fe 3 O 4 / Eu(BA) 3Phen / PVP magneto-optical dual-function composite nanofibers [Journal of Nanoparticle Research, 2012, 14(10): 1203-1209] and magneto-optical dual-function Fe 3 O 4 / Eu(BA) 3 Phen / PMMA composite nanobelts [National Invention Patent, Application No.: 201110303031.0; Optical Materials, 2013, 35(3), 526-530]; Dong Xiangting et al. prepared Eu(BA) using a single spinneret and electrospinning technology 3 Phen / PANI / PVP optoelectronic dual-functional composite nanofibers [Journal of Chemistry in Universities, 2012, 33(8), 1657-1662]; Dong Xiangting et al. prepared Eu(BA) using two-strand parallel electrospinning technology 3 Phen / PVP / / PANI / PVP optoelectronic dual-function two-strand parallel nanofiber bundle [National Invention Patent, Application No.: 201210407369.5]; Dong Xiangting et al. prepared Fe 3 O 4 / PVP / / Eu(BA) 3 Phen / PVP magneto-optical dual-function two-strand parallel composite nanofiber bundle [National Invention Patent, Application No.: 201110249651.0]; Dong Xiangting et al. used a three-strand parallel spinneret and three-strand parallel electrospinning technology to prepare [Tb(BA) 3 phen / PMMA] / / [PANI / PMMA] / / [Fe 3 O 4 / PMMA] anisotropic electromagnetic-optical trifunctional tricolor flag-shaped nanoribbons and their arrays [Chinese invention patent, authorization number: ZL201410795606.9; Materials&Design, 2021, 211, 11012]; Guoyi Wang, et al used conjugated electrospinning technology to prepare [Fe 3 O 4 / PVP)] / / [Tb(BA) 3 phen / PVP] magneto-optical dual-function Janus nanofibers [RSCAdvances, 2019, 9, 206-214]. At present, there is no new conjugated electrospinning technology that combines two-strand parallel electrospinning technology with single-axis electrospinning technology to construct {[CsPbBr 3 / PS] / / [CoFe 2 O 4 / PS]}||[CsPb(Br 0.06 / I 0.94 )3 / PS] related reports on tricolor flag-type micron fibers.
[0007] When using electrospinning technology to prepare nanomaterials, the type of raw materials, the molecular weight of the polymer template, the composition of the spinning solution, the spinning process parameters and the structure of the spinneret have an important influence on the morphology and size of the final product. The present invention adopts electrospinning technology, uses a [single-axis needle] / / [single-axis needle] two parallel spinnerets composed of two 8# stainless steel syringe needles and an 8# stainless steel syringe needle as a single-axis spinneret, and adds polystyrene PS to CsPbBr 3 The quantum dots were prepared into a mixed solution of dichloromethane DCM solution and ethyl acetate EtOAc to prepare a spinning solution I, which is a spinning solution with green fluorescence function; CoFe 2 O 4 Nanocrystals and PS were added to a mixed solvent of DCM and EtOAc to prepare a spinning solution II, which is a spinning solution with magnetic function; polystyrene PS was added to CsPb (Br 0.06 / I 0.94 ) 3 The quantum dots are mixed in a dichloromethane DCM solution and an ethyl acetate EtOAc solution to prepare a spinning solution III, which is a spinning solution with red fluorescence function. The conjugate electrospinning is performed using positive and negative high-voltage DC power supplies, and the spinning solution I and the spinning solution II are respectively added to a syringe connected to two parallel spinnerets, the spinneret is connected to the positive electrode of the positive high-voltage power supply, and the spinning solution III is added to a syringe connected to a single-axis spinneret, the spinneret is connected to the negative electrode of the negative high-voltage power supply, and a rotating drum is used as a receiving device. Under the optimal process conditions, {[CsPbBr 3 / PS] / / [CoFe 2 O 4 / PS]}||[CsPb(Br 0.06 / I 0.94 ) 3 / PS] tricolor flag-type micron fiber. In this special one-dimensional structure, the two perovskite quantum dots are distributed on both sides of the magnetic material, achieving effective separation and avoiding direct contact, preventing the halogen anion exchange of the two perovskite quantum dots due to direct contact and blending to produce other perovskite quantum dots that will affect the fluorescence properties of the material, thereby ensuring the excellent fluorescence properties of the material. At the same time, the two perovskite quantum dots are effectively separated from the magnetic material, avoiding the adverse effects of the magnetic material on the luminescence of the perovskite quantum dots, and giving the fiber good magnetism. Therefore, the prepared micron fiber has excellent fluorescence and magnetic dual functional properties and will have important application prospects. Summary of the invention
[0008] In the background technology, a single spinneret was used to prepare polyvinyl pyrrolidone / ferroferric oxide composite magnetic nanofibers, PAN / Eu(BA) 3 Phen composite luminescent nanofibers, Fe 3 O 4 / Eu(BA) 3 phen / PVP and Fe 2 O 3 nanoparticles / Eu(DBM) 3 (Bath) / PAN composite dual-functional magneto-optical nanofibers; Eu(BA) was prepared by electrospinning technology using two parallel spinnerets 3 Phen / PVP / / PANI / PVP photoelectric dual-function two-strand parallel nanofiber bundle and Fe 3 O 4 / PVP / / Eu(BA) 3 Phen / PVP magneto-optical dual-functional two-strand parallel composite nanofiber bundles; [Fe 3 O 4 / PVP)] / / [Tb(BA) 3 phen / PVP] magneto-optical bifunctional Janus nanofibers were prepared by electrospinning technology; a three-strand parallel spinneret was used to prepare [Tb(BA) 3 phen / PMMA] / / [PANI / PMMA] / / [Fe 3 O 4 [CsPbBr / PMMA] anisotropic electromagnetic light-conducting trifunctional tricolor flag-shaped nanobelts and their arrays. The raw materials, templates, solvents and final target products used are different from those of the method of the present invention. The present invention adopts a new conjugated electrospinning technology that combines two-strand parallel electrospinning technology with single-axis electrospinning technology to construct {[CsPbBr 3 / PS] / / [CoFe 2 O 4 / PS]}||[CsPb(Br 0.06 / I 0.94 ) 3 / PS] The tricolor flag-like micron fiber adds a new morphology and new structure material to the fiber field and provides a new technology for manufacturing tricolor flag-like micron fiber.
[0009] The present invention is implemented by first synthesizing CsPbBr by hot injection method. 3 and CsPb(Br 0.06 / I 0.94 ) 3 Dichloromethane DCM solution of perovskite quantum dots, CoFe prepared by precipitation method 2 O4 Nanocrystals; adding polystyrene PS to CsPbBr 3 The quantum dots were prepared into a spinning solution I in a mixed solution of dichloromethane DCM solution and ethyl acetate EtOAc; CoFe 2 O 4 Nanocrystals and PS were added to a mixed solvent of DCM and EtOAc to prepare spinning solution II; polystyrene PS was added to CsPb(Br 0.06 / I 0.94 ) 3 The quantum dots are prepared into a spinning solution III in a mixed solution of a dichloromethane (DCM) solution and an ethyl acetate (EtOAc); a positive and a negative high-voltage DC power supply are used for conjugated electrospinning, and spinning solution I and spinning solution II are respectively added into a syringe connected to two parallel spinnerets, the spinneret is connected to the positive electrode of the positive high-voltage power supply, and spinning solution III is added into a syringe connected to a single-axis spinneret, the spinneret is connected to the negative electrode of the negative high-voltage power supply, a rotating drum is used as a receiving device, and a new conjugated electrospinning technology combining two parallel electrospinning technology with single-axis electrospinning technology is used to prepare {[CsPbBr 3 / PS] / / [CoFe 2 O 4 / PS]}||[CsPb(Br 0.06 / I 0.94 ) 3 / PS] tricolor flag type micron fiber, the steps are:
[0010] (1) Synthesis of CsPbBr by hot injection 3 Perovskite quantum dots
[0011] 1.2 mmol Cs 2 CO 3 , 1.5 mL of oleic acid OA and 18.5 mL of octadecene ODE were added to a 50 mL three-necked flask, heated to 120 ° C under nitrogen protection and maintained for 1 h, then heated to 150 ° C and maintained for 0.5 h until the white powder was completely dissolved to obtain a transparent and clear cesium oleate solution; 0.4 mmol PbBr 2 and 20 mL of octadecene ODE were added to a 100 mL three-necked flask and kept at room temperature in a nitrogen atmosphere for 1 h. The solution was then heated to 120 °C and kept for 0.5 h for dehydration. After that, 2 mL of oleic acid OA and 2 mL of oleylamine OAm were added to the solution and heated to 180 °C until PbBr 2After the mixture was completely dissolved, 2 mL of cesium oleate at 120 ° C was quickly injected into the solution. After reacting for 5 seconds, the mixed solution was placed in an ice water bath to cool to terminate the growth of nanocrystals. The cooled solution was centrifuged and the obtained precipitate was dispersed in 10 mL of dichloromethane DCM to form CsPbBr 3 / DCM solution;
[0012] (2) Preparation of CoFe by precipitation method 2 O 4 Nanocrystals
[0013] Dissolve 40.2 g of NaOH in 600 mL of distilled water, stir and heat to boiling to form a NaOH solution, add 0.08 mmol of Co(Ac) 2 ·4H 2 O and 0.16mmol Fe(NO 3 ) 3 9H 2 O was added to 100 mL of distilled water, stirred at 60 °C until completely dissolved, and then the solution was slowly poured into a boiling NaOH solution, stirred at 80 °C for 1 h; a dilute nitric acid solution with a volume ratio of 1:1 was added to the mixed solution, the pH value was adjusted to 4.8, and after stirring for 0.5 h, 0.1 mL of oleic acid OA was dropwise added to the mixed solution to obtain a black precipitate, which was centrifuged, washed three times with distillation, and dried at 60 °C for 24 h to obtain CoFe 2 O 4 Nanocrystals;
[0014] (3) Synthesis of CsPb(Br) by hot injection 0.06 / I 0.94 ) 3 Perovskite quantum dots
[0015] 1.2 mmol Cs 2 CO 3 , 1.5 mL of oleic acid OA and 18.5 mL of octadecene ODE were added to a 50 mL three-necked flask, heated to 120 °C under nitrogen protection and maintained for 1 h, then heated to 150 °C and maintained for 0.5 h until the white powder was completely dissolved to obtain a transparent and clear cesium oleate solution; 0.5 mmol PbI 2 、0.03mmol CaBr 2 and 20 mL of octadecene ODE were added to a 100 mL three-necked flask and kept at room temperature in a nitrogen atmosphere for 1 h. The solution was then heated to 120 °C and kept for 0.5 h for dehydration. After that, 2 mL of oleic acid OA and 2 mL of oleylamine OAm were added to the solution and heated to 180 °C until PbI 2 and CaBr 2After the mixture was completely dissolved, 2 mL of cesium oleate at 120 ° C was quickly injected into the solution. After reacting for 5 seconds, the mixed solution was placed in an ice water bath to cool to terminate the growth of nanocrystals. The cooled solution was centrifuged and the obtained precipitate was dispersed in 10 mL of dichloromethane DCM to form CsPb (Br 0.06 / I 0.94 ) 3 / DCM solution;
[0016] (4) Preparation of spinning solution
[0017] 6 mL of CsPbBr 3 / DCM solution and 4 mL of ethyl acetate EtOAc were mixed, and then 2.0 g of polymer template polystyrene PS with a molecular weight of 200000 was added, and stirred at room temperature for 4 h to obtain spinning solution I; 3.0 g of CoFe 2 O 4 The nanocrystals were uniformly dispersed in a mixed solvent of 6 mL DCM and 4 mL EtOAc by ultrasonication, and then 2.0 g of a polymer template polystyrene PS with a molecular weight of 200,000 was added and stirred at room temperature for 4 h to obtain a spinning solution II. 6 mL of CsPb(Br 0.06 / I 0.94 ) 3 / DCM solution and 4 mL of EtOAc were mixed, and then 2.0 g of a polymer template polystyrene PS with a molecular weight of 200,000 was added, and stirred at room temperature for 4 h to obtain a spinning solution III;
[0018] (5) Preparation of {[CsPbBr 3 / PS] / / [CoFe 2 O 4 / PS]}||[CsPb(Br 0.06 / I 0.94 ) 3 / PS] tricolor flag type micron fiber: two 8# stainless steel needles with flat tips were bent at an angle of 30° respectively, so that the two needles could be closely arranged in parallel and fixed, and then a 1mL plastic spray gun head was used to cover the two parallel stainless steel needles, so that the front ends of the two stainless steel needles were in the middle part of the plastic spray gun head, forming two parallel spinnerets, which were connected to two 10mL syringes, and the spinning solution I and the spinning solution II were added into the two syringes respectively, and the two parallel spinnerets were connected to the positive electrode of the positive DC high voltage power supply; the 8# stainless steel needle with flat tips was used as a uniaxial spinneret, which was connected to a 1 0mL syringe, add spinning solution III into the syringe, connect the uniaxial spinneret to the negative electrode of the negative DC high voltage power supply; the two spinnerets are at an angle of 45° to the horizontal plane, the distance between the two spinneret nozzles is 10cm, the receiving device is a horizontally placed cylindrical aluminum drum with a length of 20cm and a diameter of 7cm, the rotation speed is 400r / min, the spinning voltage is ±9kV, the distance between the nozzle of the jet head and the collecting drum is 15cm, the ambient temperature is 20℃-30℃, the relative humidity is 20%-50%, and after the spinning solution is completely consumed, {[CsPbBr 3 / PS] / / [CoFe 2 O 4 / PS]}||[CsPb(Br 0.06 / I 0.94 ) 3 / PS] tricolor flag type micron fiber.
[0019] The {[CsPbBr 3 / PS] / / [CoFe 2 O 4 / PS]}||[CsPb(Br 0.06 / I 0.94 ) 3 / PS] tricolor flag type micron fiber, composed of CsPbBr 3 / PS、CoFe 2 O 4 / PS and CsPb(Br 0.06 / I 0.94 ) 3 / PS three fibers are adhered together side by side to form a structure similar to a tricolor flag. The average diameter of each tricolor flag-like micron fiber is 7.61±0.07μm. Under the excitation of 365nm ultraviolet light, the sample emits bright yellow fluorescence. The saturation magnetization intensity of the sample is 10.53emu / g, and the coercive force is 336Oe. The prepared tricolor flag-like micron fiber has good dual functional properties of fluorescence and magnetism, achieving the purpose of the invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 Yes 3 / PS] / / [CoFe 2 O 4 / PS]}||[CsPb(Br 0.06 / I 0.94 ) 3 / PS] XRD spectrum of tricolor flag-type microfibers;
[0021] Figure 2 Yes 3 / PS] / / [CoFe 2 O 4 / PS]}||[CsPb(Br 0.06 / I 0.94 ) 3 / PS] SEM image of tricolor flag-like microfibers;
[0022] Figure 3 Yes 3 / PS] / / [CoFe 2 O 4 / PS]}||[CsPb(Br 0.06 / I 0.94 ) 3 / PS] Diameter distribution histogram of tricolor flag-type microfibers;
[0023] Figure 4 Is a single root {[CsPbBr 3 / PS] / / [CoFe 2 O 4 / PS]}||[CsPb(Br 0.06 / I 0.94 ) 3 / PS] energy dispersion spectrum analysis diagram of tricolor flag type micron fiber, which also serves as the abstract figure;
[0024] Figure 5 Yes 3 / PS] / / [CoFe 2 O 4 / PS]}||[CsPb(Br 0.06 / I 0.94 ) 3 / PS] emission spectrum of tricolor flag-type micron fibers;
[0025] Figure 6 Yes 3 / PS] / / [CoFe 2 O 4 / PS]}||[CsPb(Br 0.06 / I0.94 ) 3 / PS] CIE chromaticity coordinate diagram of tricolor flag type micron fiber;
[0026] Figure 7 Yes 3 / PS] / / [CoFe 2 O 4 / PS]}||[CsPb(Br 0.06 / I 0.94 ) 3 / PS] hysteresis loop diagram of tricolor flag-type micron fiber. DETAILED DESCRIPTION
[0027] The Cs selected in the present invention 2 CO 3 , oleic acid OA, octadecene ODE, oleylamine OAm, PbBr 2 , PbI 2 , CaBr 2 , dichloromethane DCM, NaOH, Co(Ac) 2 ·4H 2 O,Fe(NO 3 ) 3 9H 2 O, nitric acid, nitrogen, ethyl acetate EtOAc, and polystyrene PS with a molecular weight of 200,000 were all commercially available analytically pure products; distilled water was homemade in the laboratory; and the glass instruments and equipment used were commonly used in the laboratory.
[0028] Example: 1.2 mmol Cs 2 CO 3 , 1.5 mL of oleic acid OA and 18.5 mL of octadecene ODE were added to a 50 mL three-necked flask, heated to 120 ° C under nitrogen protection and maintained for 1 h, then heated to 150 ° C and maintained for 0.5 h until the white powder was completely dissolved to obtain a transparent and clear cesium oleate solution; 0.4 mmol PbBr 2 and 20 mL of octadecene ODE were added to a 100 mL three-necked flask and kept at room temperature in a nitrogen atmosphere for 1 h. The solution was then heated to 120 °C and kept for 0.5 h for dehydration. After that, 2 mL of oleic acid OA and 2 mL of oleylamine OAm were added to the solution and heated to 180 °C until PbBr 2 After the mixture was completely dissolved, 2 mL of cesium oleate at 120 ° C was quickly injected into the solution. After reacting for 5 seconds, the mixed solution was placed in an ice water bath to cool to terminate the growth of nanocrystals. The cooled solution was centrifuged and the obtained precipitate was dispersed in 10 mL of dichloromethane DCM to form CsPbBr 3 / DCM solution; 40.2 g NaOH was dissolved in 600 mL of distilled water, stirred and heated to boiling to form a NaOH solution, 0.08 mmol Co(Ac) 2 ·4H 2 O and 0.16mmol Fe(NO 3 ) 3 9H 2 O was added to 100 mL of distilled water, stirred at 60 °C until completely dissolved, and then the solution was slowly poured into a boiling NaOH solution, stirred at 80 °C for 1 h; a dilute nitric acid solution with a volume ratio of 1:1 was added to the mixed solution, the pH value was adjusted to 4.8, and after stirring for 0.5 h, 0.1 mL of oleic acid OA was dropwise added to the mixed solution to obtain a black precipitate, which was centrifuged, washed three times with distillation, and dried at 60 °C for 24 h to obtain CoFe 2 O 4 Nanocrystals; 1.2mmol Cs 2 CO 3 , 1.5 mL of oleic acid OA and 18.5 mL of octadecene ODE were added to a 50 mL three-necked flask, heated to 120 °C under nitrogen protection and maintained for 1 h, then heated to 150 °C and maintained for 0.5 h until the white powder was completely dissolved to obtain a transparent and clear cesium oleate solution; 0.5 mmol PbI 2 、0.03mmol CaBr 2 and 20 mL of octadecene ODE were added to a 100 mL three-necked flask and kept at room temperature in a nitrogen atmosphere for 1 h. The solution was then heated to 120 °C and kept for 0.5 h for dehydration. After that, 2 mL of oleic acid OA and 2 mL of oleylamine OAm were added to the solution and heated to 180 °C until PbI 2 and CaBr 2 After the mixture was completely dissolved, 2 mL of cesium oleate at 120 ° C was quickly injected into the solution. After reacting for 5 seconds, the mixed solution was placed in an ice water bath to cool to terminate the growth of nanocrystals. The cooled solution was centrifuged and the obtained precipitate was dispersed in 10 mL of dichloromethane DCM to form CsPb (Br 0.06 / I 0.94 ) 3 / DCM solution; 6 mL of CsPbBr 3 / DCM solution and 4 mL of ethyl acetate EtOAc were mixed, and then 2.0 g of polymer template polystyrene PS with a molecular weight of 200000 was added, and stirred at room temperature for 4 h to obtain spinning solution I; 3.0 g of CoFe 2 O 4The nanocrystals were uniformly dispersed in a mixed solvent of 6 mL DCM and 4 mL EtOAc by ultrasonication, and then 2.0 g of a polymer template polystyrene PS with a molecular weight of 200,000 was added and stirred at room temperature for 4 h to obtain a spinning solution II. 6 mL of CsPb(Br 0.06 / I 0.94 ) 3 / DCM solution and 4mL of EtOAc were mixed, and then 2.0g of a polymer template agent polystyrene PS with a molecular weight of 200000 was added, and the mixture was stirred at room temperature for 4h to obtain spinning solution III; two 8# stainless steel needles with flat tips were bent at an angle of 30° respectively, so that the two needles could be closely arranged in parallel and the two needles were fixed, and then a 1mL plastic spray gun head was used to cover the two parallel stainless steel needles, so that the front ends of the two stainless steel needles were in the middle part of the plastic spray gun head, forming two parallel spinnerets, which were connected with two 10mL syringes, and spinning solution I and spinning solution II were added into the two syringes respectively, and the two parallel spinnerets were connected to the positive electrode of a positive DC high-voltage power supply. The uniaxial spinneret is connected to a 10 mL syringe, the spinning solution III is added to the syringe, and the uniaxial spinneret is connected to the negative electrode of the negative DC high voltage power supply; the two spinnerets are at an angle of 45° to the horizontal plane, the distance between the two spinneret nozzles is 10 cm, the receiving device is a horizontally placed cylindrical aluminum drum with a length of 20 cm and a diameter of 7 cm, the speed is 400 r / min, the spinning voltage is ±9 kV, the distance between the nozzle of the jet head and the collecting drum is 15 cm, the ambient temperature is 20°C-30°C, the relative humidity is 20%-50%, and after the spinning solution is completely consumed, {[CsPbBr 3 / PS] / / [CoFe 2 O 4 / PS]}||[CsPb(Br 0.06 / I 0.94 ) 3 / PS] tricolor flag type micron fiber. 3 / PS] / / [CoFe 2 O 4 / PS]}||[CsPb(Br 0.06 / I 0.94 ) 3 / PS] tricolor flag-like microfibers containing cubic phase CoFe 2 O 4 Nanocrystals, CsPbBr 3 and CsPb(Br 0.06 / I 0.94 ) 3 Perovskite quantum dots, see Figure 1 As shown; the {[CsPbBr3 / PS] / / [CoFe 2 O 4 / PS]}||[CsPb(Br 0.06 / I 0.94 ) 3 / PS] The tricolor flag-like micron fiber has a smooth surface and good tricolor flag-like fiber morphology. Figure 2 As shown; the {[CsPbBr 3 / PS] / / [CoFe 2 O 4 / PS]}||[CsPb(Br 0.06 / I 0.94 ) 3 / PS] tricolor flag type micron fibers have an average diameter of 7.61±0.07 μm. Figure 3 As shown; Br, Fe and I elements represent CsPbBr 3 、CoFe 2 O 4 and CsPb(Br 0.06 / I 0.94 ) 3 From the EDS line analysis of a single tricolor flag-like micron fiber, it can be seen that the Br element only exists in the left half of the tricolor flag-like micron fiber, the Fe element only exists in the middle part of the tricolor flag-like micron fiber, and the I element only exists in the right half of the tricolor flag-like micron fiber. This analysis result is consistent with the structure of the tricolor flag-like micron fiber, see Figure 4 As shown in the figure, under the excitation of 356nm ultraviolet light, the tricolor flag-like micron fiber has two obvious emission peaks at 517nm and 628nm, which are from CsPbBr 3 and CsPb(Br 0.06 / I 0.94 ) 3 The characteristic luminescence of quantum dots is shown in Figure 5 As shown; under 356nm ultraviolet light excitation, {[CsPbBr 3 / PS] / / [CoFe 2 O 4 / PS]}||[CsPb(Br 0.06 / I 0.94 ) 3 / PS] tricolor flag type micron fiber emits yellow fluorescence with chromaticity coordinates of (0.4597, 0.4879), see Figure 6 As shown; the {[CsPbBr 3 / PS] / / [CoFe 2 O 4 / PS]}||[CsPb(Br 0.06 / I0.94 ) 3 / PS] tricolor flag type micron fiber has strong magnetism, saturation magnetization intensity is 10.53emu / g, coercivity is 336Oe, see Figure 7 As shown; the {[CsPbBr 3 / PS] / / [CoFe 2 O 4 / PS]}||[CsPb(Br 0.06 / I 0.94 ) 3 / PS] tricolor flag-type micron fibers have good yellow fluorescence and magnetic dual functional properties.
[0029] Of course, the present invention may have many other embodiments. Without departing from the spirit and essence of the present invention, those skilled in the art may make various corresponding changes and modifications based on the present invention, but these corresponding changes and modifications should all fall within the scope of protection of the claims attached to the present invention.
Claims
1. A preparation technology of fluorescent magnetic dual-functional tricolor flag-type micron fiber, characterized in that: The new conjugated electrospinning technology combining two-strand parallel electrospinning technology with single-axis electrospinning technology was used, polystyrene PS was used as a polymer template, dichloromethane DCM and ethyl acetate EtOAc were used as solvents, and the product {[CsPbBr3 / PS] / / [CoFe2O4 / PS]}||[CsPb(Br 0.06 / I 0.94 )3 / PS] tricolor flag type micron fiber, the steps are: (1) Synthesis of CsPbBr3 perovskite quantum dots by hot injection method 1.2 mmol Cs2CO3, 1.5 mL oleic acid OA and 18.5 mL octadecene ODE were added to a 50 mL three-necked flask, heated to 120 °C under nitrogen protection and maintained for 1 h, then heated to 150 °C and maintained for 0.5 h until the white powder was completely dissolved to obtain a transparent and clear cesium oleate solution; 0.4 mmol PbBr2 and 20 mL of octadecene ODE were added to a 100 mL three-necked flask and kept at room temperature and nitrogen atmosphere for 1 h. The solution was then heated to 120 ° C and kept for 0.5 h for dehydration. 2 mL of oleic acid OA and 2 mL of oleylamine OAm were then added to the solution and heated to 180 ° C until PbBr2 was completely dissolved. Then, 2 mL of cesium oleate at 120 ° C was quickly injected into the solution. After reacting for 5 seconds, the mixed solution was placed in an ice water bath to cool to terminate the growth of nanocrystals. The cooled solution was centrifuged and the obtained precipitate was dispersed in 10 mL of dichloromethane DCM to form a CsPbBr3 / DCM solution. (2) Preparation of CoFe2O4 nanocrystals by precipitation method 40.2 g of NaOH was dissolved in 600 mL of distilled water, stirred and heated to boiling to form a NaOH solution, 0.08 mmol of Co(Ac)2·4H2O and 0.16 mmol of Fe(NO3)3·9H2O were added to 100 mL of distilled water, stirred at 60°C until completely dissolved, and then the solution was slowly poured into the boiling NaOH solution, and stirred at 80°C for 1 h; a dilute nitric acid solution with a volume ratio of 1:1 was added to the mixed solution, and the pH value was adjusted to 4.
8. After stirring for 0.5 h, 0.1 mL of oleic acid OA was dropwise added to the mixed solution to obtain a black precipitate, which was centrifuged, washed three times with distillation, and dried at 60°C for 24 h to obtain CoFe2O4 nanocrystals; (3) Synthesis of CsPb(Br) by hot injection 0.06 / I 0.94 )3Perovskite quantum dots 1.2mmol Cs2CO3, 1.5mL oleic acid OA and 18.5mL octadecene ODE were added into a 50mL three-necked flask, heated to 120℃ and maintained for 1h under nitrogen protection, then heated to 150℃ and maintained for 0.5h until the white powder was completely dissolved to obtain a transparent and clear cesium oleate solution; 0.5mmol PbI2, 0.03mmol CaBr2 and 20 mL of octadecene ODE were added to a 100 mL three-necked flask and kept at room temperature and nitrogen atmosphere for 1 h. The solution was then heated to 120 °C and kept for 0.5 h for dehydration. 2 mL of oleic acid OA and 2 mL of oleylamine OAm were then added to the solution and heated to 180 °C until PbI2 and CaBr2 were completely dissolved. Then, 2 mL of cesium oleate at 120 °C was quickly injected into the solution. After reacting for 5 seconds, the mixed solution was placed in an ice water bath to cool to terminate the growth of nanocrystals. The cooled solution was centrifuged and the resulting precipitate was dispersed in 10 mL of dichloromethane DCM to form CsPb(Br 0.06 / I 0.94 )3 / DCM solution; (4) Preparation of spinning solution 6 mL of CsPbBr3 / DCM solution and 4 mL of ethyl acetate EtOAc were mixed, and then 2.0 g of polymer template polystyrene PS was added, and the mixture was stirred at room temperature for 4 h to obtain spinning solution I; 3.0 g of CoFe2O4 nanocrystals were ultrasonically uniformly dispersed in a mixed solvent of 6 mL of DCM and 4 mL of EtOAc, and then 2.0 g of polymer template polystyrene PS was added, and the mixture was stirred at room temperature for 4 h to obtain spinning solution II; 6 mL of CsPb(Br 0.06 / I 0.94 )3 / DCM solution and 4 mL of EtOAc were mixed, and then 2.0 g of polymer template polystyrene PS was added and stirred at room temperature for 4 h to obtain spinning solution III; (5) Preparation of {[CsPbBr3 / PS] / / [CoFe2O4 / PS]}||[CsPb(Br 0.06 / I 0.94 )3 / PS] tricolor flag type micron fiber Bend two 8# stainless steel needles with flat tips at an angle of 30° respectively, so that the two needles can be closely arranged in parallel and fixed, and then use a 1mL plastic spray gun head to cover the two parallel stainless steel needles, so that the front ends of the two stainless steel needles are in the middle part of the plastic spray gun head, forming two parallel spinnerets, which are connected to two 10mL syringes, and spinning solution I and spinning solution II are added to the two syringes respectively, and the two parallel spinnerets are connected to the positive electrode of the positive DC high-voltage power supply; use a 8# stainless steel needle with a flat tip as a single-axis spinneret, which is connected to a 10mL syringe, and spinning solution III is added to the syringe In the process, a uniaxial spinneret is connected to the negative electrode of a negative DC high voltage power supply; the two spinnerets are at an angle of 45° to the horizontal plane, the distance between the two spinneret nozzles is 10 cm, the receiving device is a horizontally placed cylindrical aluminum drum with a length of 20 cm and a diameter of 7 cm, the rotation speed is 400 r / min, the spinning voltage is ±9 kV, the distance between the nozzle of the jet head and the collecting drum is 15 cm, the ambient temperature is 20°C-30°C, the relative humidity is 20%-50%, and after the spinning solution is completely consumed, {[CsPbBr3 / PS] / / [CoFe2O4 / PS]}||[CsPb(Br 0.06 / I 0.94 )3 / PS] tricolor flag type micron fiber, composed of CsPbBr3 / PS, CoFe2O4 / PS and CsPb(Br 0.06 / I 0.94 )3 / PS three fibers are adhered together shoulder to shoulder to form a structure similar to a tricolor flag. The average diameter of each tricolor flag-like micron fiber is 7.61±0.07μm. Under the excitation of 365nm ultraviolet light, the tricolor flag-like micron fiber emits bright yellow fluorescence. The saturation magnetization intensity of the tricolor flag-like micron fiber is 10.53emu / g, and the coercive force is 336Oe. The tricolor flag-like micron fiber has good dual functional properties of fluorescence and magnetism.
2. The preparation technology of a fluorescent magnetic dual-functional tricolor flag-type micron fiber according to claim 1 is characterized in that: The polymer template is polystyrene PS with a molecular weight Mr=200000.
Citation Information
Patent Citations
Method for preparing magneto-optical difunctional two parallel strand composite nanofiber bundle
CN102433610A
Magneto-optic dual-function composite nanobelt and its preparation method
CN102504805A
Method for constructing photoelectricity double function two-stranded parallel nanometer fiber bundle
CN102943317A
Anisotropic conductive electro-optical trifunctional tricolor flag nanoribbon array and preparation method thereof
CN104532393B
Robot joint transmission structure with long service life
CN215286995U